The Process and Output of Family Resilience on Lebak Flash Flood Victims in 2020 Who Stay in Temporary Housing: Process and Output of Family Resilience on Lebak Flash Flood Victims in 2020 Who Stay in Temporary Housing - Euis Sunarti; Nurdewi Azizah Safitri (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2022)
The flash flood disaster that hit Lebak Regency in 2020 caused the family to be in a state of crisis. Families need a process to survive and come back empowered. This study aims to analyze the process and output of the resilience of the victims' families using the RESILIENSI-GA instrument. The research design was a cross-sectional study and a retrospective study. The sample was selected by purposive sampling, precisely 60 victims’ families who stay in temporary housing at Lebak Regency. Collected data in March 2021, 15 month post-disaster. The data was processed using descriptive, correlation, and multiple regression tests. The results showed that the family experienced a crisis after the disaster for 3.5 months. The process of family resilience at 15 months is better than a 1-month post-disaster. The regression test results showed that in the 15 month, family organization capacity and family atmosphere, which is a part of the process of family resilience, consistently influenced the increase of family resilience output (subjective). Meanwhile, the older the husband affects, the decrease in family resilience output (subjective). The result of this study is expected to provide data and information for policy and program makers to reinforce family resilience in dealing with disasters.